Harnessing Host-Vector Microbiome for Sustainable Plant Disease Management of Phloem-Limited Bacteria - Trivedi, Pankaj; Trivedi, Chanda; Grinyer, Jasmine; Anderson, Ian C.; Singh, Brajesh K. (Frontiers in Plant Science, 2016)
Plant health and productivity is strongly influenced by their intimate interaction with deleterious and beneficial organisms, including microbes and insects. Of the various plant diseases, insect-vectored diseases are of particular interest, including those caused by obligate parasites affecting plant phloem such as Candidatus (Ca.) Phytoplasma species and several species of Ca. Liberibacter. Recent studies on plant-microbe and plant-insect interactions of these pathogens have demonstrated that plant-microbe-insect interactions have far reaching consequences for the functioning and evolution of the organisms involved. These interactions take place within complex pathosystems and are shaped by a myriad of biotic and abiotic factors. However our current understanding of these processes and their implications for the establishment and spread of insect-borne diseases remains limited. This article highlights the molecular, ecological, and evolutionary aspects of interactions among insects, plants, and their associated microbial communities with a focus on insect vectored and phloem-limited pathogens belonging to Ca. Phytoplasma and Ca. Liberibacter species. We propose that innovative and interdisciplinary research aimed at linking scales from the cellular to the community level will be vital for increasing our understanding of the mechanisms underpinning plant-insect-microbe interactions. Examination of such interactions could lead us to applied solutions for sustainable disease and pest management.